Interpersonal Communication of Interfaith Couples in Maintaining Family Harmony - Andrew Samuel; Dilmai Putra; Aldila Vidianingtyas Utami (Utami Publisher, 2026)
This study aims to understand interpersonal communication among interfaith couples in maintaining harmonious family relationships in Rama Agung Village, North Bengkulu. Interfaith marriage represents a social reality within Indonesia’s multicultural society, characterized by differences in values, beliefs, and religious practices in family life. These differences may potentially lead to conflict if not managed through effective communication. This research employed a qualitative approach with a phenomenological method to explore the lived experiences of couples in building family harmony. Data were collected through in-depth interviews, non-participant observation, and documentation, involving the interfaith couple as primary informants and extended family members as supporting informants. Data analysis was conducted through data reduction, coding, theme development, and essence description. The findings indicate that effective interpersonal communication—characterized by openness, empathy, positiveness, supportiveness, and equality—serves as the primary foundation for maintaining family harmony. In addition, the socially tolerant village environment strengthens the stability of interfaith family relationships. Therefore, family harmony is not determined by religious similarity but by the consistent quality of interpersonal communication established within the family.